Homozygous PKP2 deletion associated with neonatal left ventricle noncompaction. Issue 1 (26th April 2016) - Ramond, F.; Janin, A.; Di Filippo, S.; Chanavat, V.; Chalabreysse, L.; Roux‐Buisson, N.; Sanlaville, D.; Touraine, R.; Millat, G.
Abstract : Left ventricular noncompaction cardiomyopathy (LVNC) is a clinically heterogeneous disorder characterized by a trabecular meshwork and deep intertrabecular myocardial recesses that communicate with the left ventricular cavity. Several genetic causes of LVNC have been reported, with variable modes of inheritance, including autosomal dominant and X‐linked inheritance, but relatively few responsible genes have been identified. A NGS workflow, based on a panel of 95 genes developed for sequencing most prevalent sudden cardiac death‐causing genes, was used to make a rapid and costless molecular diagnosis in two siblings with a severe noncompaction cardiomyopathy starting prenatally and leading to rapid cardiac failure. For the first time, a total homozygous PKP2 deletion was identified. This molecular defect was further confirmed by MLPA and array‐comparative genomic hybridization (CGH). Heterozygous PKP2 mutations are usually reported in a significant proportion of Arrhythmogenic Right Ventricular Cardiomyopathy cases. Our results show, for the first time, the involvement of PKP2 in severe cardiomyopathy with ventricular non compaction. Abstract :